1978
DOI: 10.1084/jem.147.3.645
|View full text |Cite
|
Sign up to set email alerts
|

Immunological unresponsiveness to native dextran B512 in young animals of dextran high responder strains is due to lack of Ig receptors expression. Evidence for a nonrandom expression of V-genes.

Abstract: Young mice of dextran high responder strains were found to be complete nonresponders to the alpha-1-6 epitope of dextran during 30-40 days after birth. They also failed to respond to thymus-dependent dextran-protein conjugates. Cells from young and adult mice were activated equally well to polyclonal antibody synthesis by the polyclonal B-cell-activating property of dextran. There was no age difference in the immune response to haptens conjugated to dextran, indicating that dextran can function as an efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

1979
1979
1997
1997

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 12 publications
2
28
0
Order By: Relevance
“…Although mechanisms have been defined that can readily account for an extraordinarily diverse antibody repertoire (1-7), previous studies have indicated that neonatal mice have a relatively limited repertoire and that repertoire diversity is gradually acquired in a highly reproducible manner within an inbred murine strain (21)(22)(23)(24). To investigate the characteristics of early neonatal antibodies and probe the mechanisms that may be responsible for repertoire acquisition, we have established two hybridoma cell lines derived from neonatal B cells antigenically stimulated in an CONTROI, OF NEONATAL ANTIBODY EXPRESSION irradiated adoptive host.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although mechanisms have been defined that can readily account for an extraordinarily diverse antibody repertoire (1-7), previous studies have indicated that neonatal mice have a relatively limited repertoire and that repertoire diversity is gradually acquired in a highly reproducible manner within an inbred murine strain (21)(22)(23)(24). To investigate the characteristics of early neonatal antibodies and probe the mechanisms that may be responsible for repertoire acquisition, we have established two hybridoma cell lines derived from neonatal B cells antigenically stimulated in an CONTROI, OF NEONATAL ANTIBODY EXPRESSION irradiated adoptive host.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most striking features of the immune mechanism is the extraordinary reproducibility of repertoire expression (19)(20)(21)(22)(23)(24). Thus, in spite of the extremely complex mechanisms available for diversification and clonotype selection, repertoire sharing appears to be the rule among genetically identical individuals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these data and theoretical considerations, Burnet (3) proposed that the ability to distinguish self from non-self results from the deletion of self reactive clones during the early stages of the immune system development. This concept was supported by experiments that showed an impaired ability to produce specific antibodies following neonatal injection of large amounts of foreign antigens (4,5) or antibodies specific for idiotypic, allotypic or isotypic determinants of Ig receptors (6)(7)(8). Furthermore, Etlinger and Chiller (9) showed that aggregated human gammaglobulin, a highly immunogenic T-dependent antigen in euthymic mice, was able to induce immune specific unresponsiveness when injected into newborn mice.…”
Section: Introductionmentioning
confidence: 52%
“…Neonatal injection with antibodies specific for immunoglobulin (Ig) antigenic determinants caused a long lasting suppression of the B cells that express the corresponding determinant (6)(7)(8). Furthermore, injection of large amounts of bacterial polysaccharides (4,5) or T-dependent antigens (9) impaired the subsequent synthesis of specific antibodies.…”
Section: Immune Responsiveness Of the Neonatal B Cellsmentioning
confidence: 99%